2006
DOI: 10.1177/014860710603000121
|View full text |Cite
|
Sign up to set email alerts
|

A Carbohydrate‐Rich Beverage Prior to Surgery Prevents Surgery‐Induced Immunodepression: A Randomized, Controlled, Clinical Trial

Abstract: This study suggests that preoperative intake of a carbohydrate-rich beverage can prevent surgery-induced immunodepression and thus might reduce the risk of infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 32 publications
3
42
0
4
Order By: Relevance
“…Studies have demonstrated that the metabolic responses, including the IR, were significantly attenuated or abolished by the administration of CHO 2 h before elective open general or gastrointestinal surgery, total hip replacement, and thyroidectomy, primarily owing to a decreased reduction in peripheral glucose disposal and increased glucose oxidation rates [2,[13][14][15][16][17][18][19][20]. Preoperative administration of oral CHO could significantly reduce the length of the hospital stay and recovery time as compared with fasting or consumption of a placebo (flavored water) [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that the metabolic responses, including the IR, were significantly attenuated or abolished by the administration of CHO 2 h before elective open general or gastrointestinal surgery, total hip replacement, and thyroidectomy, primarily owing to a decreased reduction in peripheral glucose disposal and increased glucose oxidation rates [2,[13][14][15][16][17][18][19][20]. Preoperative administration of oral CHO could significantly reduce the length of the hospital stay and recovery time as compared with fasting or consumption of a placebo (flavored water) [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, it is used 12.5% maltodextrin (200-400 ml), two hours before surgery with safety. Studies have shown benefits in reducing the loss of muscle mass and strength, reduced anxiety, hunger and thirst, beyond the maintenance of immune function in the postoperative period [21][22][23]. Aguilar-Nascimento et al [7] investigated the rate of postoperative nausea and vomiting (PONV) in surgical patients, and found a lower rate of these complications in those who used CHO solution preoperatively.…”
Section: Introductionmentioning
confidence: 99%
“…Because the study solution (OS-1) used in the present study contains 2.5% carbohydrate, serum glucose concentrations following treatment were within normal limits. It has been reported that carbohydrate loading before surgery minimizes postoperative insulin resistance and postoperative immune suppression, thus helping to reduce postoperative complications [21,22]; the oral intake of fl uids containing an appropriate carbohydrate content is therefore considered to be a suitable means of providing a source of carbohydrates.…”
Section: Discussionmentioning
confidence: 99%